IoT-Based LPG Gas Leak Detection System for Real-Time Household Safety Monitoring Integrated with Telegram Bot Notifications - Nur Afiyat; Ellys Kumala Pramartaningthyas; Arif Prasetyo (G-Tech: Jurnal Teknologi Terapan, 2026)
Liquefied Petroleum Gas (LPG) is widely utilized as a primary energy source in household and industrial applications. However, gas leakage remains a major safety concern that can lead to fire or explosion hazards. This study presents the design and implementation of an Internet of Things (IoT)-based LPG leakage detection system equipped with real-time alert notifications via the Telegram application to enhance household safety. The proposed system integrates a NodeMCU V3 ESP8266 microcontroller programmed using the Arduino IDE and an MQ-2 gas sensor capable of detecting gas concentrations between 300 and 10,000 ppm. Performance evaluation was conducted through experimental testing that measured key parameters such as gas concentration detection accuracy, system response time, and data transmission latency. When the detected gas concentration exceeds the threshold of 300 ppm, the system automatically transmits an alert message to the user’s smartphone through Telegram. The results show that the system effectively detects gas leakage events with an average response time of 23.018 seconds and an average data transmission delay of 265.76 milliseconds, remaining below the 300-millisecond standard. The novelty of this research lies in the integration of IoT-based gas monitoring with real-time Telegram bot notifications optimized for household environments, offering a more responsive and user-friendly solution compared to previous detection systems. These findings demonstrate that the developed system provides an effective and reliable approach for early detection and prevention of LPG gas leak hazards.